Numerical-experimental investigation on vibration and bending failure of stiffened composite plates - Quoc, Tran Huu; Thinh, Tran Ich (Vietnam Journal of Mechanics, 2010)
In this paper, free vibration and bending of laminated stiffened glass fiber/polyester composite plates with laminated open section (rectangular or T shaped) and closed section (hat shaped) of stiffeners have been studied by finite element method and experiment. A nine-noded isoparametric element with nine degrees of freedom per node is developed for the plates. The stiffener element is a three-noded isoparametric beam element with five degrees of freedom per node and the stiffeners can be positioned anywhere within the plate element. The natural frequencies of the laminated stiffened plates are determined experimentally by Dewebook device and DasyLab 7.0 software. The results calculated by computational model for above plates under different boundary conditions are in good agreement with experiments. The failure problems of these stiffened glass fiber/polyester composite plates are also investigated.